A case report of recurrent testicular germ cell tumor in a patient with a history of primary pulmonary germ cell tumor and a review of the literature - Tan, Jian; Wu, Jinfeng; Yuan, Runqiang; Li, Wei; Li, Linfeng; Huang, Hongxing; Lu, Yangbai (Frontiers in Oncology, 2024)
Background ： Compared to testicular germ cell tumors, the incidence of extragonadal germ cell tumors (EGCTs) is relatively low. While the lungs are a common site for metastasis of malignant germ cell tumors, primary pulmonary germ cell tumors are extremely rare. Objective ： To enhance the understanding of the diagnosis and treatment of germ cell tumors, particularly extragonadal germ cell tumors (EGCTs). Methods ： A Case Report of Recurrent Testicular Germ Cell Tumor in a Patient with Primary Pulmonary Germ Cell Tumor and a Review of the Literature Clinical data ： The patient was initially diagnosed with primary pulmonary germ cell tumor and received standard treatment. Five years later, the patient developed a recurrent testicular germ cell tumor. The pathological results from the two surgeries were different, indicating embryonal carcinoma in the first instance and seminoma in the second.For cases with a high suspicion of extragonadal germ cell tumors (EGCTs), early pathological biopsy is essential to confirm the histological subtype and to guide the selection of the most appropriate and sensitive treatment regimen.【Keywords】 Germ cell tumors；Extra-gonadal germ cell tumors；Primary pulmonary germ cell tumor；Non-seminoma germ cell tumor；Case Report